PENGARUH BRAND AMBASSADOR DAN TAGLINE GRATIS ONGKIR SHOPEE TERHADAP KEPUTUSAN PEMBELIAN - Wicaksana, Fadli Wira; Yulinda, Ade Tiara (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to Brand Ambassador and Tagline Free Shipping Shopee on Purchasing Decisions (Case Study of Shopee Consumers in University of Muhammadiyah Bengkulu). This research uses quantitative research methods. The population in this study was the University of Muhammadiyah Bengkulu, with the sampling method using the Purposive Sampling method. In the implementation of the research, 1,400 respondents were obtained randomly. In this study using data collection methods by way of observation, interviews and distributing questionnaires or questionnaires. The results of data processing, it can be concluded that brand image and lifestyle partially or simultaneously have a positive and significant effect on purchasing decisions.Keywords: Purchase decision, abassador brand, free shipping